2011
DOI: 10.1371/journal.pone.0024549
|View full text |Cite
|
Sign up to set email alerts
|

The Human Endogenous Circadian System Causes Greatest Platelet Activation during the Biological Morning Independent of Behaviors

Abstract: BackgroundPlatelets are involved in the thromboses that are central to myocardial infarctions and ischemic strokes. Such adverse cardiovascular events have day/night patterns with peaks in the morning (∼9AM), potentially related to endogenous circadian clock control of platelet activation. The objective was to test if the human endogenous circadian system influences (1) platelet function and (2) platelet response to standardized behavioral stressors. We also aimed to compare the magnitude of any effects on pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
126
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 165 publications
(131 citation statements)
references
References 36 publications
3
126
0
2
Order By: Relevance
“…Participants had 2 baseline 24-hour days in normal room lighting conditions (;90 lux wake episodes/0 lux sleep episodes), followed by a forced desynchrony protocol (FD) consisting of 12 standardized 20-hour "days" with controlled activity, posture, meals, sleep, room temperature, and light (,4 lux), as previously published. [9][10][11][12] On the second baseline day and each 20-hour day, participants underwent a standardized test battery, 12 which included a 15-minute 60°p assive head-up tilt test and a 15-minute steady-state cycle ergometer test at 60% of maximal predicted heart rate. Core body temperature derived from a rectal thermistor was continuously recorded and used to determine circadian period and phase, with minimum core body temperature assigned as 0°(equivalent to ;4:30 AM in these participants).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants had 2 baseline 24-hour days in normal room lighting conditions (;90 lux wake episodes/0 lux sleep episodes), followed by a forced desynchrony protocol (FD) consisting of 12 standardized 20-hour "days" with controlled activity, posture, meals, sleep, room temperature, and light (,4 lux), as previously published. [9][10][11][12] On the second baseline day and each 20-hour day, participants underwent a standardized test battery, 12 which included a 15-minute 60°p assive head-up tilt test and a 15-minute steady-state cycle ergometer test at 60% of maximal predicted heart rate. Core body temperature derived from a rectal thermistor was continuously recorded and used to determine circadian period and phase, with minimum core body temperature assigned as 0°(equivalent to ;4:30 AM in these participants).…”
Section: Methodsmentioning
confidence: 99%
“…[9][10][11][12] Of these factors, platelet activation and cortisol had endogenous circadian peaks, and plasma epinephrine the steepest circadian increase, during the vulnerable window for adverse cardiovascular events, around 9 AM. Furthermore, in response to exercise, the largest circadian increase in epinephrine and largest circadian decrease in cardiac vagal modulation also occurred around 9 AM.…”
Section: Org Frommentioning
confidence: 99%
“…There are reports that chronobiological disorders are detected in patients with arterial hypertension [70][71][72], diabetes mellitus [73][74][75], cardiac ischemia [11,12,14,61,66], dementia [67][68][69][70], etc. Nowadays there is a lot of data on the existence of chronobiological patterns in the development of stroke and myocardial infarction (MI) [11,12,14].…”
Section: Desynchronosis As a Risk Factor For Strokementioning
confidence: 99%
“…In the morning under free-living conditions, blood pressure increases on wake-up stress consisting of postural change associated with rising, beginning ambulation, and increased sympathetic activity 49) . Simultaneously, other physiological conditions such as endothelial function [50][51][52] and blood characteristics 53,54) also have been reported to contribute to the morning peak in adverse cardiovascular events. Data from large-scale meta-analyses have confirmed that the incidence of acute myocardial infarction 55) and sudden cardiac death 56) is two to three times more likely during the three hours after waking from nocturnal sleep than at other times of day.…”
Section: A Variety Of Human Circadian Rhythms and Characteristicsmentioning
confidence: 99%